Analysis of the effect of training on the explosive power of the pencak silat sickle kick: a comparative study of plyometric and conventional exercises - Mashud,; Sudirman, Ridwan; Samodra, Y Touvan Juni; Widiastuti,; Arini, Ira; Suharto, Taufik Hidayat; Suryadi, Didi; Wulandari, Arina; Aryadi, Dedi; Rahmat, Ayi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to find out the differences between the effects of plyometric and conventional exercises on the explosive power of the spark. This study used an experimental method where the sample is given treatment. The subjects in this study were 4th semester students of the STKIP Setiabudhi Sports Education study program. The sampling technique used cluster random sampling, so a sample of 40 students was obtained. The study was conducted for 14 meetings with a training frequency of twice a week. The sample was given treatment in the form of plyometric training to increase the explosive power of the sickle kick. The data obtained was analyzed using the SPSS version 26 application. The results of the comparison between plyometric and conventional exercises for low hand-foot coordination were reviewed. The study indicated that the value of Qcount = 12.96 exceeded Qtable = 4.90, or Qcount > Qtable, suggesting significant differences, with the plyometric exercise method proving superior to conventional exercise. Further, the results of the comparison of plyometric and conventional exercises were reviewed for high hand-foot coordination and the results showed that the value of Qcount = 6.65 was greater than Qtable = 4.90, or Qcount > Qtable, indicating significant differences favoring the plyometric exercise method over conventional exercise. The plyometric training method and the conventional training method have an influence on the explosive power of the sickle kick. However, the plyometric training method is more influential, effective, and good for the explosive power of the sickle kick than the conventional training method.